The idea of a "great Maribor" - Gostenčnik, Nina (Studia Historica Slovenica, 2016)
Interests concerning the incorporation of neighbouring municipalities to the city municipality of Maribor have increased during the period of passing the new acts on municipalities and city municipalities. One of the most important consequences of both acts was the possibility of merging smaller municipalities into bigger ones. The Maribor municipality had a chance to incorporate smaller neighbouring municipalities and therefore enlarge its territory and increase the number of residents. The article discusses the attempts and struggles of the Maribor municipality and (successful) resistance of the surrounding municipalities.
Keywords: lokalna uprava; Maribor; zakonodaja; zgodovinski pregledi